Membangun Kemandirian Ekonomi Pesantren : Tinjauan Terhadap Proteksi Ekonomi Pada Unit Usaha Di Pondok Pesantren Teknologi Pertanian Al Islam Kambitin - Azmi Azhari Primadana (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
The number of pesantren in Indonesia currently stands at 28,518, with 4,354,245 students. However, only 90.48% of the 11,686 pesantren have business units in 2020 and 2021, indicating that many pesantren do not yet have business units. To maintain the sustainability and resilience of pesantren as educational and religious institutions, they need to be economically independent to avoid outside intervention. Through economic protection policies, pesantren can fortify their economy by limiting outside competitors and maximizing internal resources. This study aims to analyze the economic protection strategy towards the economic development of pesantren in Al-Islam Agricultural Technology Boarding School using qualitative methods and SWOT analysis. The results show that the economic protection policy of this boarding school is in quadrant 1, showing the potential and strengths that can be utilized, with a strategy of supporting aggressive growth (SO).